2015
DOI: 10.1556/004.2015.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of retinoids during oocyte maturation diminishes apoptosis in caprine embryos

Abstract: Exposure of caprine oocytes and embryos to retinoids enhances embryonic development, but the mechanisms governing this phenomenon have not been characterised. The aim of the present study was to evaluate if the incidence of apoptosis is affected by the addition of retinyl acetate (RAc) and 9-cis-retinoic acid (RA) during in vitro maturation (IVM) of caprine oocytes. Embryonic development was recorded on days 3 and 8 post-fertilisation, and apoptosis was measured by caspase activity and DNA fragmentation (TUNEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…4 C and E ). For example, down-regulation of the expression of genes involved in oocyte–granulosa communication (i.e., Gja4 and Oosp1 , -2 , -3 ) and the development and survival of oocytes (i.e., Aldh1a2 ) in Mtor -GcKO oocytes could potentially affect the development and functions of oocyte-companion granulosa cells ( 37 42 ). In addition, up-regulation of several genes for mRNA decay could dysregulate the transcript dosage of certain factors key for oocyte and follicle development.…”
Section: Resultsmentioning
confidence: 99%
“…4 C and E ). For example, down-regulation of the expression of genes involved in oocyte–granulosa communication (i.e., Gja4 and Oosp1 , -2 , -3 ) and the development and survival of oocytes (i.e., Aldh1a2 ) in Mtor -GcKO oocytes could potentially affect the development and functions of oocyte-companion granulosa cells ( 37 42 ). In addition, up-regulation of several genes for mRNA decay could dysregulate the transcript dosage of certain factors key for oocyte and follicle development.…”
Section: Resultsmentioning
confidence: 99%
“…The natural metabolites of retinol (RT) such as all- trans retinoic acid (t-RA) and 9- cis RA are collectively known as retinoids and are considered as non-enzymatic antioxidants (Guerin et al , 2001). Recent protocols have used these compounds in the culture medium of embryos taking into account their deep effect upon cellular survival, proliferation, differentiation and embryonic morphogenesis (Noy, 2010; Rajesh et al , 2010; Rhinn & Dollé, 2012; Conceição et al , 2015; Conceição et al , 2016). It was found that the addition of retinoids to the culture medium enhances the subsequent preimplantation embryonic development in bovine embryos (Lima et al , 2004; Ahmed et al , 2016), and in goat embryos (Duque et al , 2002a,b; Lima et al , 2006; Chiamenti et al , 2010, 2012; Conceição et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq analysis of the mTOR depleted oocytes discovered differential expression of 979 transcripts. Gene-enrichment analysis revealed down-regulation of genes controlling key oogeneic processes, oocyte mRNA decay, epigenetic and transcriptional control, cell cycle, microtubule-related processes, oocyte–granulosa communication as well as those involved in the development and survival of oocytes companion GC [ 32 , 33 , 34 , 35 , 36 , 37 ]. Genes associated with mRNA decay that could dysregulate the transcript dosage of certain key factors for oocyte and follicle development were upregulated.…”
Section: Novel Regulators Of Fulliculogenesismentioning
confidence: 99%